Evaluating active labor market policy in Indonesia: A case study of the job loss insurance program - Muhyiddin, Muhyiddin; Wijaya, Andy Fefta; Putra, Fadillah; Wike, Wike (Edelweiss Applied Science and Technology, 2025)
Indonesia’s Job Loss Insurance Program (Jaminan Kehilangan Pekerjaan / JKP), introduced in 2022, represents a key component of the country’s Active Labor Market Policy (ALMP) agenda, designed to support formal workers affected by layoffs through cash benefits, retraining, and job placement services. This study evaluates the effectiveness of JKP using a qualitative case study approach guided by the Context–Input–Process–Product (CIPP) model. Data were collected through semi-structured interviews, focus group discussions, and document analysis across six provinces representing diverse labor market conditions. The findings reveal a disconnect between policy objectives and on-the-ground implementation, marked by institutional fragmentation, limited coordination, burdensome administrative procedures, and minimal labor market reintegration outcomes. Only 17% of participants gained employment through JKP, and 43% reported lower-quality jobs. The program’s focus on formal workers excludes over 59% of Indonesia’s labor force, limiting its equity and impact. To improve effectiveness, the study recommends cross-agency coordination, digital integration, mandatory training requirements, and inclusive pilot schemes targeting informal workers. These findings contribute to public policy and ALMP literature by demonstrating how the CIPP model can be applied to evaluate complex, multi-actor interventions in developing country contexts.